Notes on collective litigation - Silvestri, Elisabetta (Civil Procedure Review, 2024)
This essay sketches a few features of collective litigation, emphasizing the elusive character of a multifaceted phenomenon and a few critical aspects of the different models of collective litigation provided by the law in force in a variety of legal systems.